Policing, planning and sex: Governing bodies, spatially. Issue 1 (April 2013) - Crofts, Penny; Hubbard, Phil; Prior, Jason
Literatures on the regulation of conduct have tended to focus on the role of policing and the enforcement of criminal law. This paper instead emphasizes the importance of planning in shaping conduct, using the example of how planning shapes sexual conduct to demonstrate that planning can, in different times and places, exercise police-type powers. We illustrate this by analysing the regulation of brothels in Sydney and Parramatta, NSW, Australia, providing a case study of spaces of sexuality that historically were constructed and regulated as criminal, but have since become lawful. This paper examines the ways in which these transitions in law have been differently expressed and accomplished through local planning enforcement. In making such arguments, the paper emphasizes not only the potential for planners to act like police, but also the capacity of planning to supplant policing as a key technique of governmentality.